2014
DOI: 10.1002/app.40384
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched polyglycerols, obtained from environmentally benign monomer, as reactive clays inhibitors for water‐based drilling fluids

Abstract: To prevent the degradation of the borehole and also the disintegration and dispersion of drilled cuttings, different shale stabilizing additives are used in water-based drilling fluids (WBFs). Glycols, poly(ethylene glycol), glycerols, and polyglycerol derivatives, also called polyols, have been used to inhibit shales containing reactive clays in WBF. These additives are normally used in conjunction with KCl to reduce clay swelling and dispersion of drilled cuttings. Highly branched polymers have become an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The increasing of temperature has made the carboxymethylation of CBG easier, and was conducive to the smooth expansion of the product in aqueous solution, which have led to the increase of AV. [22][23][24] When the reaction temperature exceeded 50 °C, the increasing of temperature may lead to the degradation of CBG and the occurrence of side reactions, thus the performances of CCBG have decreased accordingly.…”
Section: Effect Of Reaction Temperaturementioning
confidence: 99%
“…The increasing of temperature has made the carboxymethylation of CBG easier, and was conducive to the smooth expansion of the product in aqueous solution, which have led to the increase of AV. [22][23][24] When the reaction temperature exceeded 50 °C, the increasing of temperature may lead to the degradation of CBG and the occurrence of side reactions, thus the performances of CCBG have decreased accordingly.…”
Section: Effect Of Reaction Temperaturementioning
confidence: 99%
“…Miller (2011) reported that hydrogenated poly (propylene imine) dendrimers could be used as shale hydration inhibition agents and were not hydrolyzed up to 260°C, exhibiting high temperature resistance. Teixeira et al (2014) found that the hyperbranched polyglycerols were promising environmentally friendly inhibitors in water-based drilling fluids.…”
Section: Introductionmentioning
confidence: 99%
“…However, dendrimers demand laborius multistep synthetic procedures, in contrary, polyglycerols are usually produced in simple one-step procedures (Parzuchowski et al, 2008). Teixeira et al (2014) applied hyperbranched polyglycerols obtained from glycerol carbonate, an ecofriendly precursor, in association with KCl, achieving high percentage cuttings recovery with a polymer concentration about 5 wt%. It has been demonstrated that the performance of these hyperbranched structures is superior to the ones obtained with linear PEGs.…”
Section: Introductionmentioning
confidence: 99%